Efektifitas Murottal Qur’an dan Virtual Reality terhadap kecemasan ibu hamil trimester 3 - Iin Setiawati; Rohmah, Mawadatur (Journal of Issues in Midwifery, 2023)
Anxiety is a psychological element that describes a psychological element that describes feelings, emotional state of a woman when facing the reality of her life. Based on a 2012 report, 73.5% of mothers experience anxiety in the third trimester, 46.7% mild anxiety and 53.3% moderate anxiety. Aims was to analyze the effectiveness of murottal Qur'an and Virtual Reality on the anxiety of third-trimester pregnancy. The research used a quasi-experimental research design with Nonequivalent Control Group Design approach. The sample size was 56 pregnant women, with 28 pregnant women being the control group and 28 pregnant women being the treatment group. The statistical test used was paired T test with α 0.05. in the Murottal Qur'an group there was a decrease in anxiety level of pregnancy before and after listening to murottal Qur'an, with an average decrease of 8.64, while in Virtuan Reality group there was a decrease in the anxiety level of pregnancy before and after being given Virtual Reality, with an average of 8.54. Statistical test results for before and after each group result is ρ 0.000. Statistical tests using Paired T test obtained ρ 0.000, meaning that Murottal Qur'an and Virtual Reality are effective to reducing anxiety level of third-trimester pregnancy. Murottal Qur'an and Virtual Reality are both effective to reducing anxiety level of third-trimester pregnancy